Community participation in the Kampung KB Program in Jambi Province - Hardiani Hardiani; Dwi Hastuti; Hasriati Nasution (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Kampung Keluarga Berkualitas (Kampung KB) is one of the development programs to create quality families in Indonesia. Kampung KB is a village-level regional unit with integration and convergence in implementing empowerment and strengthening of family institutions in all its dimensions to improve the quality of human resources, families, and communities. The growth of Kampung KB in Jambi Province shows the high government's attention to this program to improve the quality of life of its people. However, the Kampung KB's success in improving the community's quality of life is largely determined by the level of community participation itself. This study analyzes the factors that influence community participation in the Kampung KB Program in Jambi Province. This study uses primary data obtained through target group respondents in Kampung KB in Jambi Province. Data were analyzed using descriptive statistics and a binary logit regression model. The study results found that the overall level of community participation in the Kampung KB Program was moderate. The level of community participation was significantly related to education, length of stay at the location, and distance from house to the place of activity.